2020
DOI: 10.1128/aac.01972-19
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and Intracellular Activities of Omadacycline against Legionella pneumophila

Abstract: Omadacycline is an aminomethylcycline antibiotic with in vitro activity against pathogens causing community-acquired bacterial pneumonia (CABP). This study investigated the activity of omadacycline against Legionella pneumophila strains isolated between 1995 and 2014 from nosocomial or community-acquired respiratory infections. Omadacycline exhibited extracellular activity similar to comparator antibiotics; intracellular penetrance was found by day 3 of omadacycline exposure. These results support the utility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The intracellular activity of fluoroquinolones has been largely demonstrated against a vast array of pathogens like S. aureus, L. monocytogenes, L. pneumophila, Burkholderia thailandensis, Yersinia pseudotuberculosis, Francisella philomiragia, or Coxiella burnetii (31,(68)(69)(70). The relatively high efficacy of doxycycline (bacteriostatic in broth) is rather unexpected but has been already reported in models of intracellular infection by C. burnettii (70), Chlamydia trachomatis (71), or L. pneumophila (72), possibly suggesting that the intracellular environment may contribute to improve its killing capacity. As efficacy is a pharmacodynamic-driven parameter reflecting bacterial responsiveness to antibiotics (61), it is not surprising that the gain of efficacy triggered by NV716 does not correlate with the lipophilicity of the antibiotics (Figure S8C).…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular activity of fluoroquinolones has been largely demonstrated against a vast array of pathogens like S. aureus, L. monocytogenes, L. pneumophila, Burkholderia thailandensis, Yersinia pseudotuberculosis, Francisella philomiragia, or Coxiella burnetii (31,(68)(69)(70). The relatively high efficacy of doxycycline (bacteriostatic in broth) is rather unexpected but has been already reported in models of intracellular infection by C. burnettii (70), Chlamydia trachomatis (71), or L. pneumophila (72), possibly suggesting that the intracellular environment may contribute to improve its killing capacity. As efficacy is a pharmacodynamic-driven parameter reflecting bacterial responsiveness to antibiotics (61), it is not surprising that the gain of efficacy triggered by NV716 does not correlate with the lipophilicity of the antibiotics (Figure S8C).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, newer antibiotics that did not appear in our search at the time of the study should be evaluated for their potential intracellular effectiveness. For example, omadacycline, a novel tetracycline, seems to be effective against MRSA in osteomyelitis in a mouse model 188 and intracellularly against Legionella pneumophila, 189 even though its effectiveness seems to be pH dependent. 190 …”
Section: Discussionmentioning
confidence: 99%
“…PK data demonstrated that omadacycline has AUC0-24 in ELF and plasma 3-fold higher than tigecycline [ 117 ] and this could contribute to understanding the poor performance of tigecycline in lung infections. Given the increasing antibiotic resistance trend of intracellular bacteria, the in vitro activity of omadacycline against the Legionella [ 118 ], Mycoplasma [ 119 , 120 ], Chlamydia [ 118 ] and Rickettsia [ 121 , 122 ] species deserves to be mentioned. Omadacycline is also active in vitro against rapidly growing mycobacteria (e.g., Mycobacterium abscessus , M. fortuitum and M. chelonae ) [ 123 ] with emerging clinical data [ 124 ].…”
Section: Tetracyclinesmentioning
confidence: 99%